Study of drying kinetics of quince - Barroca, Maria João (2012)
The present work aimed at studying the influence of temperature (40, 50 and 60 ºC) and air velocity (0.7, 0.9 and 1.2 m/s) on drying of quince. From the results obtained it was possible to conclude that the quince drying had a similar kinetic behaviour, regardless of the operating conditions. As to the influence of the drying temperature on the process, it was observed that increasing the drying temperature from 40 ºC to 60 ºC leads to a diminishing of 30 % in the drying time. On the other hand the increase in air velocity does not have a proportional effect on the reduction of dimensionless moisture, particularly at higher quince moisture contents. The rate of quince drying is characterised by the absence of the constant drying-rate period followed by falling-rate period, regardless of the conditions. The data for the moisture ratio over time was fitted to different empirical models with the best performances coming from the Modified Page, Henderson & Page and Logarithmic models.